Gender differences in neural correlates of stress‐induced anxiety. Issue 1 (7th November 2016) - Seo, Dongju; Ahluwalia, Aneesha; Potenza, Marc N.; Sinha, Rajita
Abstract : Although gender differences have been identified as a crucial factor for understanding stress‐related anxiety and associated clinical disorders, the neural mechanisms underlying these differences remain unclear. To explore gender differences in the neural correlates of stress‐induced anxiety, the current study used functional magnetic resonance imaging to examine brain responses in 96 healthy men and women with commensurable levels of trait anxiety as they engaged in a personalized guided imagery paradigm to provoke stress and neutral‐relaxing experiences. During the task, a significant gender main effect emerged, with men displaying greater responses in the caudate, cingulate gyrus, midbrain, thalamus, and cerebellum. In contrast, women showed greater responses in the posterior insula, temporal gyrus, and occipital lobe. Additionally, a significant anxiety ratings × gender interaction from whole‐brain regression analyses was observed in the dorsomedial prefrontal cortex, left inferior parietal lobe, left temporal gyrus, occipital gyrus, and cerebellum ( P  < 0.05, whole‐brain family‐wise error corrected), with positive associations between activity in these regions and stress‐induced anxiety in women, but negative associations in men, indicating that men and women differentially use neural resources when experiencing stress‐induced anxiety. The findings suggest that in response to stress, there is a greater use of the medial prefrontal–parietal cortices in experiencing subjective anxiety in women, while decreased use of this circuit was associated with increased subjective anxiety states in men. The current study has implications for understanding gender‐specific differences in stress‐induced anxiety and vulnerability to stress‐related clinical disorders, and for developing more effective treatment strategies tailored to each gender. © 2016 Wiley Periodicals, Inc. Abstract : In response to stress‐induced anxiety, men and women displayed opposite patterns of neural activity in the dorsomedial prefrontal cortex, left inferior parietal lobe, left temporal gyrus, occipital gyrus, and cerebellum. The findings suggest that males and females differentially use neural resources when experiencing stress‐induced anxiety; implications are discussed.